La alteración pretriásica según el estudio de las fracciones pesadas de materiales detríticos. - Hernando Costa, S.; Hernando Costa, J. (Cuadernos de Geología Ibérica, 1977)
We have studied the heavy fractions and the light ones of the Permian detrical materjals which are found just under the base of Buntsandtein, and so tbey are afected by the pretriasic alteration we have obteined sorne results about the characteristic of Ihese alteration, and tests aboud the results of the heavy minerals tecnic and the light fraction in the study of paleosoil and pa leoalteration.